Differences in Production Costs, Production Quantity and Income of Batik Craftsmen in Recipients and Non-Recipients of ZIS Funds - Novia Damayanti, Mika; Ajeng Kartika Galuh (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The growth in the amount of zakat, infaq and sedekah (ZIS) fund collection has always increased every year, such as in 2010-2017, followed by the growth in ZIS fund distribution. Fund distribution can be either consumptive or productive. One form of fund distribution in the form of productive zakat can be distributed to batik craftsmen. There are two groups of batik craftsmen in Sumurgung Village, namely craftsmen who receive assistance and those who do not receive assistance. This study aims to analyze the differences in production costs, product quantity, and business income of two groups of batik craftsmen. The sample of this study was a group of batik craftsmen who received assistance using the full sampling method and those who did not receive assistance using the convenience sampling method. Data collection was carried out by distributing open questionnaires and interviews through observation to Sumurgung Village. The statistical method used is descriptive analysis and conducting a difference test with an independent sample t-test. The results of the study showed that there were significant differences in the variables of production costs, product quantity and business income between batik craftsmen who received assistance and batik craftsmen who did not receive assistance. Based on the results of the independent sample t-test of several variables that have been tested, batik craftsmen who did not receive assistance had higher scores compared to batik craftsmen who received assistance. The difference occurs because there are differences in production techniques between the two groups, thus having implications for differences in values ​​in each variable tested.